Study on characteristics of phosphates and transition-metal complexes synthesized onto viscose rayon felt for flame retardancy - Kim, JS; Choi, US; Ko, YG; Kim, SH (KOREAN SOC INDUSTRIAL ENGINEERING CHEMISTRY, 2002)
Phosphates (polyphosphate and ammonium phosphate) are synthesized onto the viscose rayon felt as high-performance materials for flame retardancy. This Surface reaction has advantages of non-blooming effect and application to thermosetting plastics. Metal complexes have been known to have the effect of reducing amounts of smoke. Therefore, in second step, transition metal complexes were synthesized onto the viscose rayon ammonium phosphate felt. This article focuses on Surface modification of phosphates and metal complex onto viscose rayon. All reactions were confirmed by ATR FT-IR and TOF-SIMS. As concentrations of phosphoric acid and urea increased, peak intensities of ammonium ion group and phosphate groups grew up highly. The thermal properties of the synthesized materials were studied using thermal gravimetric analysis (TGA) and oxygen index test. Oil the basis of experimental results, the synthesized materials for flame retardancy showed excellent physico-chemical and thermal effect, and found to be as the flame retardants.